2021
DOI: 10.1111/jocn.15887
|View full text |Cite
|
Sign up to set email alerts
|

‘A picture is worth a thousand words’—A photovoice study exploring health professionals’ experiences during the COVID‐19 pandemic

Abstract: Aim To elicit the experiences and perspectives of health professionals working on the frontline in the COVID‐19 pandemic. Background Although some qualitative studies have been carried out in health professionals during COVID‐19 pandemic, to our knowledge, no study has used the Photovoice method. Design A qualitative descriptive study using Photovoice was carried out between March and June 2020. Methods A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
0
19
0
1
Order By: Relevance
“…Likewise, religious leaders were allowed to use online devices to provide spiritual care during the hospitalization to alleviate the suffering of patients. These strategies were essential to minimize the problems arising from the uncertainty of the disease (Badanta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, religious leaders were allowed to use online devices to provide spiritual care during the hospitalization to alleviate the suffering of patients. These strategies were essential to minimize the problems arising from the uncertainty of the disease (Badanta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Just eight months after the World Health Organization (WHO) declared COVID-19 as a pandemic on 11 March 2020, there remained over 12,000,000 cases and 255,000 deaths from COVID-19 in the United States alone [ 3 , 4 ]. Not surprisingly, due to the overwhelming strain COVID-19 placed on frontline health care professionals, many reported fears and frustrations throughout the pandemic with regard to poor organizational management, lack of personal protective equipment, being overworked, facing high emotional demands, contracting the disease, and being stigmatized and betrayed by members of the public not employed in health care [ 2 , 5 , 6 , 7 , 8 , 9 , 10 ]. Consequently, an emerging literature base has found that frontline health care workers during COVID-19 reported feelings of increased stress, anxiety, loneliness, isolation, depression, PTSD, and sleep disturbance [ 2 , 5 , 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…These qualitative findings were similar to those found by Amakiri et al (2020) in which in the United Kingdom, families of health care workers reported feelings of uncertainty and loneliness [ 15 ]. Due to familial relationships often serving as either pillars of strength and/or a taxing relationship during times of stress, it is important to further understand if and how the COVID-19 pandemic impacted family roles and functioning for frontline health care workers [ 10 ]. In the context of this study, family functioning includes an understanding of family, routines, roles, and rules, along with the challenges and strengths.…”
Section: Introductionmentioning
confidence: 99%
“…One study from Spain has delved into the adaptation strategies that FHCWs tried as self-help strategies. 36 The authors used a photovoice strategy, where they asked participants to provide photographs that embodied how they felt during the pandemic and then interviewed them about it. Participants highlighted the use of leisure and importance of community support.…”
Section: Discussionmentioning
confidence: 99%